Orphan Children and their issues: A Study of at Jammu & Kashmir - Shakeel, Tahir (Innovative Research Thoughts, 2017)
The destiny of a kid is completely and entirely dependent on the mindset, conduct, and assets of their parents. It is possible for a family with solid economics to raise children who are well-rounded in all aspects of life. Sadly, an orphan lacks this important protector, i.e. his or her parents. Thousands of families saw the breadwinners they relied on disappear, including their breadwinners' children. It's amazing how well an orphan manages to make it in this difficult and costly world. There is a lot of stress on the orphans in Jammu and Kashmir1 because of the ongoing war that has been going on for the past two decades, with Kashmir being the most hit. Some of the country's most significant institutions have suffered infrastructure damage as a result of the war, including the loss of human resources. The number of orphans in this state is much higher than the national average. The purpose of is to shed light on the plight of orphans in the Kashmir area, as well as the obstacles they face. The government's involvement in reducing orphans and rehabilitating conflict-affected people is also mentioned.